Colour transfer between images - Bose, Rajeswari (Nanyang Technological University, 2022)
Image processing performs some operations on an image in order to modify it. Changing an image’s colour using various methods, including colour transfer, is a very recurrent task in this field. Colour transfer involves changing the overall colour scheme of a source image to match that of a target image while ensuring the scene of the source image remains the same. In this report two algorithms, by Reinhardt et al. and Pitie et al. respectively, are implemented and studied. Their performances are compared and analysed. Image histograms and colour clouds were used to provide objective comparisons. Image fidelity and naturalness are also used as subjective measures. Some use cases of colour transfer are explored as well.